Nuevas vías de marketing turístico: La figura del videojuego como medio de promoción turística de un destino - Valeria Varela Varela; Eva Sánchez Amboage (Atlantic Review of Economics (ARoEc), 2022)
– Due to the intangibility of the tourism product, which cannot be experienced before its consumption, destination promoters have used different means throughout history to communicate the characteristics of a destination and attract the attention of future tourists: mass advertising on television, brochures, public relations, websites, social media, or more recently, virtual reality, augmented reality, and video games. Sp ecifically, the exponential growth experienced in recent years by the video game industry , which has had economic and social implications of great repercussion worldwide, has positioned the video game as a potential means of communication for tourism promo tion, even influencing the destination image . T he objective of this research is to determine what are the essential elements that a video game must have to become a means of tourist promotion of a destination. To achieve the proposed objective, a qualitat ive methodology was carried out through structured interviews with experts from both sectors. Among the results of the research, it is specified that video games must be adapted to the needs of the territory, as well as to those of the target audience for tourism promotion to be effective. Also, the usefulness of video games to promote tourist destinations is considered, an option that is increasingly attractive by destination managers due to recent changes in tourism trends and the search by tourists for p laces in which they can live increasingly unique experiences.
Keywords: 330